A Novel Betaproteobacterial Agent of Gill Epitheliocystis in Seawater Farmed Atlantic Salmon (Salmo salar) - Toenshoff, Elena R. (Public Library of Science, 2012)
Epitheliocystis, a disease characterised by cytoplasmic bacterial inclusions (cysts) in the gill and less commonly skin epithelial cells, has been reported in many marine and freshwater fish species and may be associated with mortality. Previously, molecular and ultrastructural analyses have exclusively associated members of the Chlamydiae with such inclusions. Here we investigated a population of farmed Atlantic salmon from the west coast of Norway displaying gill epitheliocystis. Although ‘Candidatus Piscichlamydia salmonis’, previously reported to be present in such cysts, was detected by PCR in most of the gill samples analysed, this bacterium was found to be a rare member of the gill microbiota, and not associated with the observed cysts as demonstrated by fluorescence in situ hybridization assays. The application of a broad range 16 S rRNA targeted PCR assay instead identified a novel betaproteobacterium as an abundant member of the gill microbiota. Fluorescence in situ hybridization demonstrated that this bacterium, tentatively classified as ‘Candidatus Branchiomonas cysticola’, was the cyst-forming agent in these samples. While histology and ultrastructure of ‘Ca. B. cysticola’ cysts revealed forms similar to the reticulate and intermediate bodies described in earlier reports from salmon in seawater, no elementary bodies typical of the chlamydial developmental cycle were observed. In conclusion, this study identified a novel agent of epitheliocystis in sea-farmed Atlantic salmon and demonstrated that these cysts can be caused by bacteria phylogenetically distinct from the Chlamydiae.